The rise of promotional rhetoric in the Discussion Sections of an interdisciplinary field: a diachronic perspective - Zhu, Yumei; Li, Xuemei (Frontiers in Psychology, 2025)
In recent decades, the growing competition to publish internationally has made the Discussion section increasingly promotional, as authors interpret and evaluate their findings to highlight research significance. However, this section also risks exaggerating a study’s contribution with promotional discourse. The current study examines the diachronic changes of promotional strategies in Communication research articles (RAs) Discussion sections by analyzing two corpora from 1980 to 1981 and 2020–2021. Drawing on analytical frameworks for analyzing promotional steps and stance features, findings revealed a marked increase in the frequency of promotional steps and stance markers. The observed changes indicated a shift toward more implicit, subtle and strategical forms of persuasion. This study contributes to the study of promotional discourse in academic writing and calls for greater recognition of rhetorically modest and transparent writing practices as markers of scholarly credibility, encouraging editorial and review policies that reward integrity alongside visibility.